Comparison of Beef and Mutton Fats In Relation to Fat Extraction Yield, Melting Point, Iodine Value and Viscosity - Muhammad Abdillah Abdul Shukor (2019)
Animals are slaughtered to produce their by-products which can be well utilized for various applications in day to day human life, thus, contributing to the value of animals. Animal fats play an important role in a balanced diet and in the manufacture of food products contributing to texture and palatability. They are a valuable source of concentrated energy and essential fatty acids needed for growth and development. Animal lipids structural and storage, the structural lipids mainly phosphoglycerides, constitute between 0.5 and 1% of muscle and adipose tissue. Lipids are the major form of energy storage mainly as fat, which may constitute up to 97% of the adipose tissue of obese animals. Fats were produced by a variety of processes, generally referred to as rendering. Fatty tissues from both beef and mutton are composed of essentially three components, viz. water, protein and fat. This study focused on chemical composition of mutton fat and beef fat involving determination of iodine value, origin of fat samples by melting point method and viscosity of fat samples. The fat yield of the fat was determined after the wet rendering process. The difference in the fat recovery rates in the different studies was probably because of the different animal meat abdominal fat tissues. Iodine value was recognised to indicate the amount of unsaturated fatty acid. Determination of origin of fat samples by melting point method was focused on the fats melt at different temperatures, mainly due to their fatty acid characteristics. For viscosity, both length and saturation of fatty acids affect the arrangement of the membrane. Shorter chain fatty acids and ones with greater unsaturation are less stiff and less viscous, making the membranes more flexible.